Cerebrovascular-mediated dynamic alterations in neurovascular coupling: a key pathological mechanism of depression - Xiaoyun Yang; Jiaxin Wang; Jiahao Zhang; Mengjie Zhang; Anran Hao; Feng Guo; Xueying Huang; Jinlan Yan; Yuanjia Zheng; Yucen Xia; Taiyi Wang; Meng Zhang; et al. (Cell & Bioscience)
Abstract Neurovascular coupling (NVC) is a vital regulatory mechanism that synchronizes neural activity with vascular responses to support brain function. Although the precise mechanisms of NVC remain incompletely elucidated, its dysfunction is increasingly implicated in the pathogenesis of various neurological disorders. This review synthesizes recent advancements in understanding the vascular cascade, emphasizing key dynamic regulators of NVC, including mechanical forces and diffusible signals mediated by blood flow. We explore the intricate bidirectional interactions between the vasculature and neurons, highlighting their interdependent roles in neurovascular regulation. Using major depressive disorder (MDD) as a case study, we further discuss emerging evidence linking vascular dysfunction and impaired NVC to MDD pathophysiology. These insights position NVC as a promising therapeutic target for emotional disorders, underscoring the pivotal roles of hemodynamic signaling in neurovascular regulation.